2022
DOI: 10.1007/s10518-022-01426-8
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of soil liquefaction distribution in downtown Mashiki during 2016 Kumamoto earthquake using nonlinear site response

Abstract: Several sites located between Road No.28 and Akitsu River in downtown Mashiki were liquefied during the mainshock of the 2016 Kumamoto earthquake. According to the building damage survey results, only a few buildings were damaged in areas proximate to the Akitsu River, where liquefaction occurred, however, serious building damage occurred in neighboring regions. Therefore, the effect of soil liquefaction on strong ground motions in Mashiki should be ascertained. Moreover, the distribution of visible and invisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…During the mainshock of the 2016 Kumamoto earthquake, strong ground motions with a PGA larger than 300 cm/s 2 were widely observed in and around the earthquake source fault region (Suzuki et al 2017). Nonlinearity and liquefaction of soil deposits during the mainshock of the 2016 Kumamoto earthquake were reported (e.g., Tsuno et al 2017;Wakamatsu et al 2017;Sun et al 2022). Sun et al (2022) reported that there are several sites showing the maximum shear strains greater than 1% in downtown Mashiki.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During the mainshock of the 2016 Kumamoto earthquake, strong ground motions with a PGA larger than 300 cm/s 2 were widely observed in and around the earthquake source fault region (Suzuki et al 2017). Nonlinearity and liquefaction of soil deposits during the mainshock of the 2016 Kumamoto earthquake were reported (e.g., Tsuno et al 2017;Wakamatsu et al 2017;Sun et al 2022). Sun et al (2022) reported that there are several sites showing the maximum shear strains greater than 1% in downtown Mashiki.…”
Section: Discussionmentioning
confidence: 99%
“…Nonlinearity and liquefaction of soil deposits during the mainshock of the 2016 Kumamoto earthquake were reported (e.g., Tsuno et al 2017;Wakamatsu et al 2017;Sun et al 2022). Sun et al (2022) reported that there are several sites showing the maximum shear strains greater than 1% in downtown Mashiki. In Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation